Stakeholder Experiences and Perspectives on the Nueva Escuela Mexicana Reform in Mexican Primary Education - Nicholas Bremner; Nozomi Sakata; Lilia Sulema Bórquez Morales (MDPI AG, 2024)
Mexico has recently introduced the Nueva Escuela Mexicana (NEM) in Basic Education, which aims to create a more meaningful, contextualised, inclusive learning environment. This study examined stakeholder experiences and perspectives on the NEM in its first year of implementation. A total of 79 semi-structured individual and group interviews were conducted in 12 primary schools in three Mexican states. A total of 168 participants were interviewed: learners, teachers, head teachers, teacher trainers, and local and regional supervisors. This study found that stakeholders held a range of positive and negative views about the NEM reform. Participants reported several concerns, such as the lack of foundational knowledge developed through the new approach, doubts about certain curricular content (e.g., gender and sexuality), and a lack of explicit guidance and training. This paper offers policy recommendations, which may also be relevant to policymakers in other countries. Limitations of this study and recommendations for future studies are discussed.